IMPACT OF DRUMSTICK (MORINGA OLEIFERA) LEAF TABLET ON LIPID PROFILE OF SELECTED DIABETIC PATIENTS (International Journal of Food and Nutritional Sciences, 2015)
The present study was conducted with the objective to formulate a dehydrated green leafy tablet using drum stickleaf followed by supplementation study and to find out the impact on lipid profile of the selected diabetic patients. Theresults revealed that total cholesterol, HDL, LDL, VLDL, TGL initial and final level of control group was 217 and 214 mg/dl,43 and 45 mg/dl, 140 and 136 mg/dl, 34 and 30 mg/dl, 155 and 150 mg/dl respectively, whereas in experimental group thecorresponding parameters at initial and final stage was 227 and 211 mg/dl, 42 and 47 mg/dl, 149 and 135 mg/dl, 35 and 30 mg/dl,160 and 151 mg/dl. The results are proving drum stick leaves are suitable green leafy vegetable to improve the lipid profile ofdiabetic patients.